Method for packaging a battery device
Patent Information
- Application Number
- JP2023504327
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-30
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2040-07-30
Smart Images

Figure 0007651679000001 
Figure 0007651679000002 
Figure 0007651679000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for packaging a battery device and the resulting battery package.
[0002] Introduction Battery packs, which include multiple battery cells packed together, have become important in the electric vehicle industry. Each battery cell typically includes an electrode core, an electrolyte solution, and a metal shell, with the electrode core and electrolyte solution located within a chamber of the metal shell. The battery cells also need to be encapsulated with one or more packaging layers that provide suitable electrical insulation and mechanical protection for the battery cells. For example, the packaging layers may have good electrical insulation properties to prevent shorting of the battery cells, e.g., 10 12 It should have a volume resistivity of ohm-centimeter (ohm·cm) or better. When the battery pack is used in an electric vehicle, the packaging layer of each cell should also have balanced flexibility and hardness, as well as wear resistance properties, to withstand continuous vibration and wear over the life of the battery pack. The battery cell packaging material should also have sufficient chemical resistance to avoid potential damage caused by leakage of electrolytes or other chemicals used in the production of the battery cell. It is further desirable for the battery cell packaging layer to have a good appearance, for example, to provide a high distinctness of image (DOI) (e.g., 74 or better).
[0003] One of the conventional approaches for packaging flat batteries is to adhere a polyester film to the surface of the metal shell of the battery cell by heat-sensitive or pressure-sensitive adhesive, but this approach suffers from limitations such as air bubbles and defects caused by insufficient adhesion between the polyester film and the metal shell, which adversely affects the electrical insulation properties of the battery cell. In addition, polyester films usually have low hardness (such as about 2B pencil hardness) and cannot withstand continuous vibration and abrasion. Ultraviolet (UV) curing paints may have improved hardness, but are not suitable for packaging battery cells due to insufficient electrical insulation or mechanical properties.
[0004] Also, the battery industry has strict manufacturing requirements for safety. For example, battery manufacturers require materials with high flash points (e.g., higher than 60°C) to avoid fire hazards associated with equipment failure. Furthermore, solvent-based compositions are usually not acceptable to battery manufacturers because they contribute volatile organic compounds (VOCs) and most of the solvents, such as dimethylbenzene and methylbenzene, have flash points well below 60°C. Battery cells can only withstand baking temperatures up to 100°C, preferably 80°C or less. Therefore, it is further desirable to be able to package battery cells using existing manufacturing equipment and conditions.
[0005] It would be desirable to find a method of packaging battery cells that can replace conventional packaging methods without the problems mentioned above. Summary of the Invention
[0006] The present invention solves the problem of finding a method of packaging a battery device that can be used to replace conventional packaging approaches without the problems mentioned above.
[0007] The present invention provides a novel method for packaging a battery device with a metal shell by applying a specific water-based two-component polyurethane composition comprising an aqueous dispersion containing a hydroxyl-functional polymer and a polyisocyanate, and drying the polyurethane composition to form a packaging layer. 12 It can exhibit good electrical insulation properties while providing balanced mechanical properties such as volume resistivity (VR) of ohm-centimeter (ohm·cm) or more, impact resistance of 10 centimeters (cm) at 0.91 kilograms (kg) or more, adhesion rating of 5B, and chemical resistance of 100 times or more at film thicknesses of 30 μm to 120 μm. These properties can be measured according to the test methods described in the Examples section below. The method of the present invention also does not require a step of applying an adhesive material and can be carried out using existing manufacturing equipment as a conventional polyester film for packaging battery devices.
[0008] In a first aspect, the present invention is a method for packaging a battery device with a metal shell, the method comprising applying a water-based two-component polyurethane composition to a metal shell of a battery device and drying the applied polyurethane composition to form a packaging layer, the polyurethane composition comprising: (A) an aqueous dispersion containing a hydroxyl-functional polymer, the hydroxyl-functional polymer comprising 20% to 50% by weight of structural units of a hydroxy-functional alkyl (meth)acrylate, 0.1% to 10% by weight of structural units of an acid monomer, its salt, or a mixture thereof, and structural units of a monoethylenically unsaturated nonionic monomer, based on the weight of the hydroxyl-functional polymer; and (B) a polyisocyanate.
[0009] In a second aspect, the invention is a battery package resulting from the method of the first aspect. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An "aqueous" composition or dispersion herein means that the particles are dispersed in an aqueous medium. As used herein, "aqueous medium" means water and 0-30% by weight, based on the weight of the medium, of a solvent, such as naphtha, and water-miscible solvents such as alcohols, glycols, glycol ethers, and glycol esters, or mixtures thereof.
[0011] A "structural unit," also known as a "polymerized unit," of a specified monomer refers to the remainder of the monomer after polymerization, i.e., the polymerized monomer or the polymerized form of the monomer. For example, the structural unit of methyl methacrylate is: [ka] where the dotted lines represent the points of attachment of the structural units to the polymer backbone.
[0012] Water-based two-component polyurethane compositions useful in the present invention include two components: Part A and Part B, where Part A includes an aqueous dispersion of one or more hydroxyl-functional polymers, and Part B includes one or more polyisocyanates. As used herein, the term "water-based" composition refers to a composition in which the liquid medium (or carrier liquid) is water or a mixture of water and 0 to 50% by weight of a solvent, based on the weight of the liquid medium. For example, the liquid medium may include more than 60% by weight water, more than 70% by weight water, more than 80% by weight water, or more than 90% by weight water, based on the total weight of the liquid medium.
[0013] The hydroxyl functional polymer in the aqueous dispersion can be a polymer made by solution polymerization or an emulsion polymer. The hydroxyl functional polymer useful in the present invention comprises one or more structural units of hydroxy functional alkyl (meth)acrylate. Suitable hydroxy functional alkyl (meth)acrylates can include, for example, hydroxyethyl (meth)acrylates such as 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate; hydroxypropyl (meth)acrylates such as 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, and 3-hydroxypropyl methacrylate; hydroxybutyl (meth)acrylates such as 3-hydroxybutyl acrylate, 3-hydroxybutyl methacrylate, 4-hydroxybutyl acrylate, and 4-hydroxybutyl methacrylate; 6-hydroxyhexyl acrylate; 6-hydroxyhexyl methacrylate; 3-hydroxy-2-ethylhexyl acrylate; 3-hydroxy-2-ethylhexyl methacrylate; or mixtures thereof. Preferred hydroxy-functional alkyl (meth)acrylates include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, or mixtures thereof. The hydroxyl functional polymer may comprise hydroxy-functional alkyl (meth)acrylate structural units in an amount of 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, 30% or more, 31% or more, or even 32% or more by weight based on the weight of the hydroxyl functional polymer, while being 50% or less, 48% or less, 45% or less, 44% or less, 43% or less, 42% or less, 41% or less, 40% or less, 39% or less, 38% or less, 37% or less, 36% or less, 35% or less, or even 34% or less by weight.
[0014] Hydroxyl-functional polymers useful in the present invention include structural units of one or more acid monomers, their salts, or mixtures thereof, such as carboxylic acid monomers, sulfonic acid monomers, phosphorus-containing acid monomers, their salts, or mixtures thereof. Examples of suitable phosphorus-containing acid monomers and their salts include phosphoalkyl (meth)acrylates, such as phosphoethyl (meth)acrylate, phosphopropyl (meth)acrylate, phosphobutyl (meth)acrylate, their salts, or mixtures thereof; CH2=C(R1)-C(O)-O-(R2O) q-P(O)(OH)2 (wherein R1 = H or CH3, R2 = alkylene such as an ethylene group, a propylene group, or a combination thereof, q = 1 to 20), such as SIPOMER PAM-100, SIPOMER PAM-200, SIPOMER PAM-300, SIPOMER PAM-600, and SIPOMER PAM-4000 (all available from Solvay); phosphoalkoxy (meth)acrylates such as phosphoethylene glycol (meth)acrylate, phosphodiethylene glycol (meth)acrylate, phosphotriethylene glycol (meth)acrylate, phosphopropylene glycol (meth)acrylate, phosphodipropylene glycol (meth)acrylate, phosphotripropylene glycol (meth)acrylate, salts thereof, or mixtures thereof. Preferred phosphorus-containing acid monomers and their salts are selected from the group consisting of phosphoethyl (meth)acrylate, phosphopropyl (meth)acrylate, phosphobutyl (meth)acrylate, allyl ether phosphate, their salts, or mixtures thereof, and more preferably phosphoethyl methacrylate (PEM). The carboxylic acid monomers may be α,β-ethylenically unsaturated carboxylic acids, monomers having acid-forming groups that generate or can be subsequently converted to such acid groups (e.g., anhydrides, (meth)acrylic anhydride, or maleic anhydride), or mixtures thereof. Specific examples of carboxylic acid monomers include acrylic acid, methacrylic acid, maleic acid, itaconic acid, crotonic acid, fumaric acid, 2-carboxyethyl acrylate, or mixtures thereof. The sulfonic acid monomers and their salts may include sodium vinyl sulfonate (SVS), sodium styrene sulfonate (SSS), acrylamido-methyl-propane sulfonate (AMPS), and their salts, or mixtures thereof. Preferred acid monomers are selected from acrylic acid, methacrylic acid, itaconic acid, or mixtures thereof.The hydroxyl functional polymer may comprise structural units of acid monomers and salts thereof in an amount of 0.1 wt% or more, 0.3 wt% or more, 0.5 wt% or more, 0.8 wt% or more, 1.0 wt% or more, 1.3 wt% or more, 1.5 wt% or more, 1.7 wt% or more, or even 2.0 wt% or more, while at the same time 10 wt% or less, 8.0 wt% or less, 7.0 wt% or less, 6.0 wt% or less, 5.0 wt% or less, 4.5 wt% or less, 4.0 wt% or less, 3.5 wt% or less, 3.0 wt% or less, or even 2.5 wt% or less, based on the weight of the hydroxyl functional polymer.
[0015] Hydroxyl-functional polymers useful in the present invention may contain structural units of one or more ethylenically unsaturated functional monomers having at least one functional group selected from amide, acetoacetate, carbonyl, ureido, silane, or amino groups. Suitable ethylenically unsaturated functional monomers include, for example, amino-functional monomers such as dimethylaminoethyl methacrylate, dimethylaminoethyl acrylate, dimethylaminopropyl methacrylate, and dimethylaminopropyl acrylate; ureido-functional monomers such as hydroxyethyl ethylene urea methacrylate, SIPOMER WAM; hydroxyethyl ethylene urea acrylates such as II; monomers having an acetoacetate functional group such as acetoacetoxyethyl methacrylate (AAEM), acetoacetoxyethyl acrylate, acetoacetoxypropyl methacrylate, acetoacetoxypropyl acrylate, allyl acetoacetate, acetoacetoxybutyl methacrylate, acetoacetoxybutyl methacrylate, acetoacetamidoethyl methacrylate, acetoacetamidoethyl acrylate; monomers having a carbonyl-containing group such as diacetone acrylamide (DAAM) and diacetone methacrylamide; monomers having an amide functional group such as acrylamide and methacrylamide; vinyltrialkoxysilanes such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, or (meth)acryloxyalkyltrimethoxysilanes such as (meth)acryloxyethyltrimethoxysilane and (meth)acryloxypropyltrimethoxysilane; or mixtures thereof. Hydroxyl-functional polymers may contain structural units of ethylenically unsaturated functional monomers in an amount of 0 or more, 0.1 or more, 0.5 or more, 1 or more, 1.5 or more, or even 2 or more by weight, based on the weight of the hydroxyl-functional polymer, while typically 10 or less, 8 or less, 6 or less, 5 or less, or even 3 or less by weight.
[0016] The hydroxyl functional polymers useful in the present invention contain structural units of one or more monoethylenically unsaturated nonionic monomers different from the monomers mentioned above. In this specification, "nonionic monomer" refers to a monomer that does not have an ionic charge at pH=1-14. The monoethylenically unsaturated nonionic monomers can include vinyl aromatic monomers, alkyl (meth)acrylates, acrylonitrile, or mixtures thereof. Suitable vinyl aromatic monomers can include, for example, styrene; substituted styrenes such as methylstyrene, alpha-methylstyrene, trans-beta-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, butylstyrene, and p-methoxystyrene; o-, m-, and p-methoxystyrene; and p-trifluoromethylstyrene; or mixtures thereof. The alkyl (meth)acrylates can be any of the C1-C 20 Alkyl, C1-C 18 Alkyl, C1-C 12The alkyl (meth)acrylate may be an alkyl or a C1-C4 alkyl (meth)acrylate. Specific examples of alkyl (meth)acrylate include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, iso-butyl acrylate, iso-butyl methacrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, tert-butyl cyclohexyl methacrylate, trimethylcyclohexyl methacrylate, isobornyl methacrylate, isobornyl acrylate, tetrahydrofuran methacrylate, dicyclopentadienyl acrylate, dicyclopentadienyl methacrylate, and combinations thereof. The monoethylenically unsaturated nonionic monomer preferably comprises styrene in combination with one or more alkyl (meth)acrylates. Preferred monoethylenically unsaturated nonionic monomers are styrene, methyl methacrylate, cyclohexyl methacrylate, tert-butyl methacrylate, butyl acrylate, 2-ethylhexyl acrylate, or mixtures thereof. The hydroxyl functional polymer may contain structural units of monoethylenically unsaturated nonionic monomers in an amount of 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, 50% by weight or more, 55% by weight or more, or even 60% by weight or more, while at the same time 80% by weight or less, 77% by weight or less, 75% by weight or less, 74% by weight or less, or even 72% by weight or less, based on the weight of the hydroxyl functional polymer.
[0017] Hydroxyl-functional polymers useful in the present invention may contain structural units of one or more polyethylenically unsaturated monomers, including di-, tri-, tetra-, or higher polyfunctional ethylenically unsaturated monomers. Examples of suitable polyethylenically unsaturated monomers include butadiene, allyl (meth)acrylate, divinylbenzene, ethylene glycol dimethacrylate, butylene glycol dimethacrylate, or mixtures thereof. Hydroxyl-functional polymers may contain structural units of polyethylenically unsaturated monomers in an amount of 0-5% by weight, for example, 3% or less, 1% or less, 0.5% or less, or even zero, based on the weight of the hydroxyl-functional polymer.
[0018] Hydroxyl functional polymers useful in the present invention have a molecular weight of 50,000 g / mol or less, e.g., 5,000 g / mol or more, 6,000 g / mol or more, 7,000 g / mol or more, 8,000 g / mol or more, 9,000 g / mol or more, 10,000 g / mol or more, 11,000 g / mol or more, 12,000 g / mol or more, 13,000 g / mol or more, 14,000 g / mol or more, 15,000 g / mol or more, 16,000 g / mol or more, 17,000 g / mol or more, 18,000 g / mol or more, e.g., 19,000 g / mol or more, 20,000 g / mol or more, 21,000 g / mol or more, 22,000 g / mol or more, 23,000 g / mol or more, 24,000 g / mol or more, 25,000 g / mol or more, 26,000 g / mol or more, 27,000 g / mol or more, 28,000 g / mol or more, 29,000 g / mol or more, 30,000 g / mol or more, 31,000 g / mol or more, 32,000 g / mol or more, 33,000 g / mol or more, 34,000 g / mol or more, 35,000 g / mol or more, 36,000 g / mol or more, 37,000 g / mol or more, 38,000 g / mol or more, 39,000 g / mol or more, 40,000 g / mol or more, 41,000 g / The weight average molecular weight of the hydroxyl functional polymers herein can be 50,000 g / mol or less, 48,000 g / mol or less, 45,000 g / mol or less, 42,000 g / mol or less, 40,000 g / mol or less, 38,000 g / mol or less, 35,000 g / mol or less, 32,000 g / mol or less, 30,000 g / mol or less, 28,000 g / mol or less, 25,000 g / mol or less, 23,000 g / mol or less, or even 20,000 g / mol or less. The weight average molecular weight of the hydroxyl functional polymers herein can be determined by gel permeation chromatography (GPC), as described in the Examples section below.
[0019] The hydroxyl functional polymer particles dispersed in the aqueous dispersion may have a particle size of 30 to 500 nanometers (nm), for example, 50 nm or more, 60 nm or more, 70 nm or more, or even 80 nm or more, while at the same time 300 nm or less, 200 nm or less, 150 nm or less, 120 nm or less, or even 100 nm or less. The particle size herein may be measured by a Brookhaven BI-90 Plus Particle Size Analyzer.
[0020] The hydroxyl functional polymer useful in the present invention may be present in an amount of 20% to 70% by weight, 30% to 55% by weight, 35% to 50% by weight, or 40% to 45% by weight, based on the total weight of the aqueous dispersion (A).
[0021] Aqueous dispersions containing hydroxyl-functional polymers useful in the present invention can be prepared by free radical polymerization, such as solution or emulsion polymerization, of a monomer mixture containing a hydroxyl-functional alkyl (meth)acrylate, an acid monomer and / or its salt, a monoethylenically unsaturated nonionic monomer, and optionally an ethylenically unsaturated functional monomer in a liquid medium. The hydroxyl-functional polymer is preferably an emulsion polymer, i.e., prepared by emulsion polymerization.
[0022] Aqueous dispersions containing hydroxyl-functional polymers can be prepared by solution polymerizing the monomer mixture and subsequently dispersing the resulting hydroxyl-functional polymer in water before, during, or after the addition of a neutralizing agent. The solution polymerization is typically carried out at temperatures ranging from 40 to 200°C, 60 to 180°C, or 80 to 160°C. It is optional to use a small amount of organic solvent, for example, in an amount of 0 to 5% by weight of the finished dispersion of hydroxyl-functional polymer. Suitable solvents can include, for example, alcohols, ethers, alcohols containing ether groups, esters, ketones, non-polar hydrocarbons, or mixtures thereof. The solvent used can be partially removed by distillation. A preferred solution polymerization is a two-stage addition comprising a first step (I) of forming a first stage polymer and a subsequent step (II) of forming a second stage polymer in the presence of the reaction mixture obtained from step (I). The first stage polymer may comprise structural units of hydroxy functional monomers in an amount of 2.8% to 70%, 3.5% to 45%, or 23% to 38% by weight based on the weight of the first stage polymer, and structural units of acid monomers and salts thereof in an amount of zero to 1.5%, zero to 0.6%, and zero to 0.45% by weight based on the weight of the second stage polymer. The second stage polymer may comprise structural units of hydroxy functional monomers in an amount of 4.5% to 47%, 4.5% to 44%, or 11.5% to 38% by weight based on the weight of the second stage polymer, and structural units of acid monomers and salts thereof in an amount of 1.5% to 6%, 2% to 5.5%, or 2.1% to 4.5% by weight based on the weight of the second stage polymer. The amounts of monomers in the two polymer preparations are selected such that the weight ratio of the first stage polymer from step (I) to the second stage polymer from step (II) is in the range of 10:1 to 1:2 or 6:1 to 2:1.
[0023] Aqueous dispersions containing hydroxyl functional polymers can be prepared by emulsion polymerization in an aqueous medium, preferably in the presence of a surfactant. The surfactant may be added before or during the polymerization of the monomers or combinations thereof. A portion of the surfactant may also be added after polymerization. These surfactants can be anionic or nonionic, preferably anionic surfactants such as sulfate surfactants, sulfonate surfactants, or mixtures thereof. These surfactants can be used in a total amount of 0.1 wt% or more, 0.3 wt% or more, 0.5 wt% or more, 0.7 wt% or more, 0.9 wt% or more, or even 1.2 wt% or more, while 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, or even 1.5 wt% or less, based on the total weight of the monomer mixture for preparing the hydroxyl functional polymer. The monomer mixture may be added neat, as an emulsion in water, or may be added in one or more portions or continuously, linearly or non-linearly, over the reaction period to prepare the hydroxyl functional polymer. The total concentration of monomers in the monomer mixture to prepare the hydroxyl functional polymer is equal to 100%. For each monomer, the weight concentration of the monomer in the monomer mixture (i.e., based on the total weight of the monomer mixture) is the same as the weight concentration of the structural unit of such monomer in the hydroxyl functional polymer (i.e., based on the weight of the hydroxyl functional polymer). Suitable temperatures for emulsion polymerization may be below 100°C, in the range of 10-95°C, or in the range of 50-92°C. Multi-stage emulsion polymerization may be used using the above monomers, whereby at least two stages are formed successively, usually forming a multi-stage polymer comprising at least two polymer compositions.
[0024] In the polymerization process, a free radical initiator can be used. The polymerization process may be a thermally initiated or redox initiated emulsion polymerization. Examples of free radical initiators suitable for emulsion polymerization include hydrogen peroxide, t-butyl hydroperoxide, cumene hydroperoxide, ammonium and / or alkali metal persulfate, sodium perborate, perphosphoric acid and its salts, potassium permanganate, and ammonium or alkali metal salts of peroxydisulfate, or mixtures thereof. Examples of initiators suitable for solution polymerization include organic peroxides such as di-tert-butyl peroxide or tert-butylperoxy-2-ethylhexanoate, azo compounds such as azodiisobutyronitrile (AIBN), or mixtures thereof. Free radical initiators can typically be used at levels of 0.01% to 3.0% by weight, based on the total weight of the monomers.
[0025] A redox system comprising the above-mentioned initiators together with a suitable reducing agent can be used in the polymerization process, preferably emulsion polymerization. Examples of suitable reducing agents include sodium formaldehyde sulfoxylate, ascorbic acid, isoascorbic acid, alkali metal and ammonium salts of sulfur-containing acids (such as sulfites, bisulfites, thiosulfates, hydrosulfites, sulfides, hydrogen sulfides or dithionites, formadinesulfinic acid, acetonate bisulfites, etc.), glycolic acid, hydroxymethanesulfonic acid, glyoxylic acid hydrate, lactic acid, glyceric acid, malic acid, tartaric acid, and salts of the aforementioned acids. Metal salts of iron, copper, manganese, silver, platinum, vanadium, nickel, chromium, palladium, or cobalt may be used to catalyze the redox reaction. Chelating agents for metals may be used.
[0026] In order to control the molecular weight of the hydroxyl functional polymer produced by emulsion polymerization, one or more chain transfer agents may be used in the polymerization process.Examples of suitable chain transfer agents include 3-mercaptopropionic acid, methyl 3-mercaptopropionate, butyl 3-mercaptopropionate, n-dodecyl mercaptan, n-hexadecanethiol, tert-dodecyl mercaptan, n-octadecanethiol, benzenethiol, azelaic acid alkyl mercaptan, hydroxyl group-containing mercaptan, such as hydroxyethyl mercaptan, mercaptopropionic acid, or mixtures thereof. The chain transfer agent may be used in an amount effective to control the molecular weight of the hydroxyl functional polymer, for example, greater than 0.3 weight percent, 0.4 weight percent to 20 weight percent, 0.5 weight percent to 15 weight percent, 0.6 weight percent to 13 weight percent, 0.8 weight percent to 10 weight percent, 1 weight percent to 8 weight percent, 1.3 weight percent to 6 weight percent, 1.5 weight percent to 4 weight percent, 1.5 weight percent to 3 weight percent, or 2.0 weight percent to 2.5 weight percent based on the total weight of the monomer mixture.
[0027] After the polymerization process is completed, the resulting hydroxyl functional polymer dispersion may be neutralized with one or more bases as neutralizing agents, for example to a pH value of at least 5, 5.5-10, 6.0-9, 6.2-8, 6.4-7.5, or 6.6-7.2. In solution polymerization, at least a portion of the acid groups present are converted to their salt form by adding a suitable neutralizing agent before, during, or after dispersing the hydroxyl functional polymer in water. Examples of suitable bases include ammonia; alkali metal or alkaline earth metal compounds such as sodium hydroxide, potassium hydroxide, calcium hydroxide, zinc oxide, magnesium oxide, sodium carbonate, and aluminum hydroxide; N-methylmorpholine, triethylamine, ethyldiisopropylamine, N,N-dimethylethanolamine, N,N-dimethylisopropanolamine, N-methyldiethanolamine, diethylethanolamine, butanolamine, 2-aminomethyl-2-methylpropanol, isophoronediamine, triethylamine, ethylamine, propylamine, monoisopropylamine, monobutylamine, hexylamine, ethanolamine, and the like. and mixtures thereof.
[0028] The types and levels of the above monomers may be selected such that the resulting hydroxyl functional polymer has a glass transition temperature (Tg) in the range of 10-80° C., 15-75° C., 20-70° C., 25-65° C., 30-60° C., 35-55° C., or 40-50° C. As used herein, “Tg” may be determined by differential scanning calorimetry (DSC) according to the test method described in the Examples section below.
[0029] In addition to the hydroxyl functional polymer, the aqueous dispersion (A) in the polyurethane composition may further comprise one or more alcohol alkoxylates. Preferably, the aqueous dispersion comprises an emulsion polymer and one or more alcohol alkoxylates. The alcohol alkoxylates useful in the present invention are represented by the formula (I): [ka] (In the formula, R 1 is C6-C 18 A branched aliphatic group, preferably R 1 contains 8 to 18 carbon atoms, 8 to 16 carbon atoms, 8 to 14 carbon atoms, 10 to 14 carbon atoms, or 12 to 14 carbon atoms, more preferably R 1 is 2-ethylhexyl or [ka] (In the formula, R a and R b are each independently C1-C 17 an aliphatic group, provided that R a and R b containing a total of 7 to 17 carbon atoms, 7 to 15 carbon atoms, 7 to 13 carbon atoms, or 11 to 13 carbon atoms; R 2 is hydrogen, a C1-C4 linear or branched aliphatic group, or benzyl, preferably hydrogen; R 3 and R 4 are each independently hydrogen or a C1-C6 aliphatic group, provided that R 3and R 4 contains 1 to 6 carbon atoms in total, preferably R 3 and R 4 are each independently hydrogen, methyl, or ethyl; R 5 and R 6 are each independently hydrogen or a C1-C6 aliphatic group, provided that R 5 and R 6 contains 1 to 6 carbon atoms in total, preferably R 5 and R 6 are each independently hydrogen, methyl, or ethyl; x is an average value ranging from 0 to 10, 0 to 8, 2 to 7, or 3 to 6; y is an average value in the range of 5 to 15, 5 to 14, 6 to 13, or 7 to 12; z is an average value ranging from 0 to 5, 0 to 4, 0.5 to 3.5, or 1 to 3; where x+z>0.
[0030] "Aliphatic group" refers to a hydrocarbon chain (e.g., an alkyl group). In formula (I), the sum of x, y, and z can be a value sufficient to give the alcohol alkoxylate a desired molecular weight, for example, 5.5 to 20, 7 to 17, 8 to 16, or 9 to 15.
[0031] Alcohol alkoxylates useful in the present invention may be in the range of 1,000 grams per mole (g / mol), e.g., 400 g / mol or more, 420 g / mol or more, 440 g / mol or more, 450 g / mol or more, 460 g / mol or more, 480 g / mol or more, 500 g / mol or more, 520 g / mol or more, 550 g / mol or more, 560 g / mol or more, 580 g / mol or more, 600 g / mol or more, 620 g / mol or more, or more than 620 g / mol. The molecular weight of the alcohol alkoxylate may be 56100 (mg / mol) or more, 650 g / mol or more, 660 g / mol or more, or even 680 g / mol or more, and at the same time 980 g / mol or less, 960 g / mol or less, 950 g / mol or less, 940 g / mol or less, 920 g / mol or less, 910 g / mol or less, 900 g / mol or less, 880 g / mol or less, 860 g / mol or less, 850 g / mol or less, 840 g / mol or less, or even 820 g / mol or less. Molecular weight herein refers to the number average molecular weight (Mn) and is calculated by 56100 (mg / mol) / OHV (mg KOH / g), where OHV represents the hydroxyl number of the alcohol alkoxylate as determined by ASTM D4274-2011.
[0032] Alcohol alkoxylates useful in the present invention may contain ethylene oxide units (and, as ethylene oxide chains, -(CH2CH2-O)-) in an amount of 25% by weight or more, 26% by weight or more, 27% by weight or more, 28% by weight or more, 29% by weight or more, 30% by weight or more, 32% by weight or more, 35% by weight or more, 38% by weight or more, 40% by weight or more, 42% by weight or more, 45% by weight or more, 48% by weight or more, or even 50% by weight or more, based on the weight of the alcohol alkoxylate, while at the same time containing 75% by weight or less, 72% by weight or less, 70% by weight or less, 68% by weight or less, 67% by weight or less, 66% by weight or less, 65% by weight or less, or even 64% by weight or less.
[0033] Alcohol alkoxylates useful in the present invention are represented by the formula (I), 3 and R 4 are different and each independently represent hydrogen or methyl, z is 0, and the sum of x and y is 7 to 14. 1is 2-ethylhexyl. More preferably, the ethylene oxide units are present in an amount of from 30% to 70% by weight, or from 35% to 60% by weight, based on the weight of the alcohol alkoxylate.
[0034] Alcohol alkoxylates useful in the present invention have the structure of formula (I), 5 and R 6 are different and each independently represent hydrogen or ethyl, x is 0, y is 7 to 14, and z is 1 to 2. 1 teeth, [ka] (In the formula, R a and R b is as defined above, for example, R a and R b contains a total of 11 to 13 carbon atoms. More preferably, the ethylene oxide units are present in an amount of 40% to 70% or 45% to 68% by weight, based on the weight of the alcohol alkoxylate.
[0035] Alcohol alkoxylates useful in the present invention may be 2% or more, 2.1% or more, 2.2% or more, 2.3% or more, 2.4% or more, 2.5% or more, 3% or more, 3.5% or more, 4% or more, 4.5% or more, 5% or more, 5.5% or more, 6% or more, 6.5% or more, 7% or more, 7.5% or more, 8% or more, 8.5% or more by weight based on the weight of the hydroxyl functional polymer. The hydroxyl functional polymer may be present in the aqueous dispersion (A) in an amount of 20% by weight or less, 19% by weight or less, 18% by weight or less, 17% by weight or less, 16% by weight or less, 15% by weight or less, 14.5% by weight or less, 14% by weight or less, 13.5% by weight or less, 13% by weight or less, 12.5% by weight or less, 12% by weight or less, 11.5% by weight or less, 11% by weight or less, or even 10.5% by weight or less. The hydroxyl functional polymer is preferably an emulsion polymer (i.e., a hydroxyl functional emulsion polymer). Surprisingly, the combination of a hydroxyl functional emulsion polymer with an alcohol alkoxylate of formula (I) can provide many advantages to the packaging layer for a battery device, including improved electrical insulation and impact resistance properties over using a hydroxyl functional polymer prepared by solution polymerization alone, or a higher DOI than using a hydroxyl functional emulsion polymer alone.
[0036] A portion of the alcohol alkoxylate may be added prior to or during the polymerization of the monomer mixture used to prepare the hydroxyl functional polymer or combination thereof, and the remainder of the alcohol alkoxylate is added after polymerization. Preferably, all of the alcohol alkoxylate in the polyurethane composition is mixed with the hydroxyl functional polymer after its polymerization.
[0037] The polyurethane composition useful in the present invention further comprises (B) one or more polyisocyanates useful as crosslinkers. "Polyisocyanate" refers to any isocyanate-functional molecule having two or more isocyanate (NCO) groups. The polyisocyanate may be aliphatic, cycloaliphatic, aromatic, or mixtures thereof. The polyisocyanate may have an average functionality of >2 or from 2.5 to 10. Examples of suitable polyisocyanates include aliphatic diisocyanates and their dimers and trimers, such as tetramethylene diisocyanate and hexamethylene diisocyanate (HDI), 1,12-dodecane diisocyanate, 2,2,4-trimethyl-hexamethylene diisocyanate, 2,4,4-trimethyl-hexamethylene diisocyanate, 2-methyl-1,5-pentamethylene diisocyanate, and the like, C2-C8 alkylene diisocyanates. alicyclic diisocyanates and their dimers and trimers, such as isophorone diisocyanate (IPDI) and dicyclohexylmethane diisocyanate (HMDI), 1,4-cyclohexane diisocyanate and 1,3-bis-(isocyanatomethyl)cyclohexane; aromatic diisocyanates and their dimers and trimers, such as toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI). Preferably, the polyisocyanate comprises an aliphatic polyisocyanate. More preferably, the polyisocyanate is a hexamethylene diisocyanate homopolymer, a hexamethylene diisocyanate adduct, an isophorone diisocyanate homopolymer, an isophorone diisocyanate adduct, or a mixture thereof.Trimers (or isocyanurates) in polyisocyanates can be prepared by methods known in the art, for example, as disclosed in US Patent Publication No. 2006 / 0155095(A1), by trimerizing cycloaliphatic diisocyanates (e.g., isophorone diisocyanate) in the presence of one or more trimerization catalysts, such as tertiary amines or phosphines, or heterogeneous catalysts, and optionally in the presence of solvents and / or auxiliaries, such as cocatalysts, conveniently at elevated temperatures, until the desired NCO content is reached, followed by deactivation of the catalyst using inorganic and organic acids, the corresponding acid halides and alkylating agents, and preferably heating. Isocyanurate compositions containing isocyanurates from aliphatic diisocyanates can be formed by cyclizing aliphatic diisocyanates in the presence of one or more trimerization catalysts, followed by deactivation of the catalyst. Any of the isocyanurates may be further modified by conventional methods to contain urethane, urea, imino-s-triazine, uretonimine, or carbodiimide moieties.Preferably, the polyisocyanates useful in the present invention are selected from the group consisting of aliphatic diisocyanates, their dimers and trimers, or mixtures thereof.
[0038] The polyisocyanates useful in the present invention may include one or more polyisocyanate prepolymers, which may be formed by reaction of bis(isocyanotomethyl)cyclohexane and / or another aliphatic diisocyanate with a monol, diol, diamine, or monoamine, which are then modified by reaction of additional isocyanates to form allophanate or biuret modified prepolymers. Such prepolymers may further include polyalkoxy or polyether chains. Alternatively, such prepolymers may then be mixed with a trimerization catalyst to obtain an allophanate or biuret modified polyisocyanate isocyanurate composition. The preparation of such allophanate or biuret prepolymers and subsequent trimerization are known in the art, see, for example, U.S. Pat. Nos. 5,663,272 and 6,028,158. Suitable polyisocyanates may be modified with ionic compounds, such as aminosulfonic acids.
[0039] The polyisocyanates useful in the present invention may be used alone or may be diluted with one or more solvents (also referred to as "diluting solvents") to form a polyisocyanate solution prior to mixing with Part A. Suitable solvents may reduce the viscosity of the polyisocyanate and have no reactivity with the polyisocyanate. The solvent may be used in an amount of 5% to 150%, 15% to 130%, 20% to 120%, or 30% to 100% by weight based on the weight of the polyisocyanate. Suitable diluting solvents may include, for example, propylene glycol diacetate, propylene glycol methyl ether acetate, dipropylene glycol dimethyl ether, or mixtures thereof.
[0040] The polyurethane compositions useful in the present invention may have an equivalent ratio of the total number of isocyanate group equivalents in the polyisocyanate, which may contain several different polyisocyanates, to the total number of hydroxyl group equivalents in the aqueous dispersion containing the hydroxyl-functional polymer and, optionally, the alcohol alkoxylate, ranging from, for example, 0.7:1 to 4:1, 0.8:1 to 3:1, 0.9:1 to 2.5:1, or 1:1 to 1.5:1.
[0041] The polyurethane composition useful in the present invention may include one or more catalysts to accelerate curing. The catalyst may be any suitable catalyst for two-component polyurethane compositions, including metal-based catalysts such as tin-, bismuth-, zinc-, aluminum-, zirconium-containing catalysts, or tertiary amine catalysts, including aliphatic and cycloaliphatic tertiary amine catalysts that are mono-, di-, or tri-amines, or mixtures thereof. Examples of suitable metal-based catalysts include dibutyltin dilaurate, dibutyltin mercaptide, dibutyltin sulfide, dimethyltin mercaptide, dibutyltin mercaptoester, zirconium dionate, Al dionate, bismuth neodecanoate, and zinc amine compounds. Suitable tertiary amine catalysts can include, for example, triethylenediamine, triethyleneamine, 1,4-diazabicyclo[2.2.2]octane, 6-(dibutylamino)-1,8-diazabicyclo[5.4.0]undec-7-ene, dimethylcyclohexylamine, or mixtures thereof. The catalyst can be present in an amount of 0.01% to 2.5% or 0.1% to 1.0% by weight based on the total polyisocyanate and hydroxyl group-containing component solids (e.g., hydroxyl functional polymer, and optionally alcohol alkoxylate).
[0042] The polyurethane composition useful in the present invention may include one or more pigments. The term "pigment" herein refers to a particulate inorganic or organic material that can substantially contribute to the opacity, color, or hiding power of the coating. The pigment may be present in Part A of the polyurethane composition. Typically, inorganic pigments having a refractive index greater than 1.8 may include, for example, titanium dioxide (TiO2), zinc oxide, zinc sulfide, iron oxide, barium sulfate, barium carbonate, or mixtures thereof. Examples of suitable organic pigments include phthalo blue, phthalo green, monoazo yellow, carbon black, or mixtures thereof. A preferred pigment used in the present invention is TiO2. The polyurethane composition may include one or more extenders. The term "extender" refers to a particulate material having a refractive index less than or equal to 1.8 and greater than 1.3. Examples of suitable extenders include calcium carbonate, aluminum oxide (Al2O3), clay, calcium sulfate, aluminosilicates, silicates, zeolites, mica, diatomaceous earth, solid or hollow glass, ceramic beads, and opaque polymers, such as ROPAQUE™ Ultra E available from The Dow Chemical Company (ROPAQUE is a trademark of The Dow Chemical Company), or mixtures thereof. The polyurethane composition may have a pigment volume concentration (PVC) of 0-75%, 5-50%, or 10-30%. PVC can be determined by the following formula: PVC=[volume (pigment+extender) / volume (pigment+extender+binder)]×100%.
[0043] The polyurethane compositions useful in the present invention may further comprise one or more coalescent agents. The term "coalescent agent" herein refers to a solvent that fuses polymer particles into a continuous film under ambient conditions. Examples of suitable coalescent agents include dipropylene glycol n-butyl ether, propylene glycol n-butyl ether, propylene glycol methyl ether, 2-n-butoxyethanol, dipropylene glycol methyl ether, propylene glycol n-propyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, triethylene glycol monobutyl ether, dipropylene glycol n-propyl ether, n-butyl ether, aromatic hydrocarbons such as the Solvesso series from ExxonMobil, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate such as the Texanol ester alcohols from Eastman, or mixtures thereof. The coalescent agent may be present in an amount of 0% to 50%, 5% to 40%, or 10% to 25% by weight based on the weight of the hydroxyl functional polymer.
[0044] The polyurethane compositions useful in the present invention may further include conventional additives such as, for example, light stabilizers, ultraviolet (UV) absorbing compounds, leveling agents, wetting agents, dispersants, neutralizing agents, defoamers, or rheology modifiers, or mixtures thereof. These additives may be present in Part A. The polyurethane compositions may include these additives in amounts of 0 to 20% by weight, 1 to 10% by weight, based on the weight of the polyurethane composition.
[0045] The polyurethane composition useful in the present invention can be prepared by mixing an aqueous dispersion containing a hydroxyl functional polymer and optionally an alcohol alkoxylate in part A with a polyisocyanate in part B and optional ingredients such as a pigment. The polyisocyanate in part B is preferably diluted with a solvent. Part A and part B can be mixed immediately before application to form a polyurethane composition. The polyurethane composition can contain an amount of volatile organic compounds of 400 grams per liter (g / L) or less, 350 g / L or less, 330 g / L or less, 300 g / L or less, 280 g / L or less, 250 g / L or less, 210 g / L or less, 150 g / L or less, 100 g / L or less, or even 50 g / L or less, as measured according to GB30981-2020 (China National Standard for Limit of Harmful Substances of Industrial Protective Coating). The use of the polyurethane composition allows the method of the present invention to be carried out by using existing manufacturing equipment for packaging battery devices with metal shells. A battery device, typically a battery cell, may include an electrode core, an electrolyte solution, and a metal shell, with the electrode core and the electrolyte solution located within a chamber of the metal shell.
[0046] The method of packaging a battery device of the present invention includes mixing (A) an aqueous dispersion containing a hydroxyl-functional polymer with (B) a polyisocyanate to form a polyurethane composition and applying the polyurethane composition to a metal shell of the battery device. The metal shell is generally a layer of metal foil that can act as an airtight barrier around the battery device. The metal can be aluminum or an alloy thereof. The battery device can include a battery cell, preferably a lithium-based cell. The battery cell is generally flat and rectangular, such as a flat battery. The polyurethane composition can be applied to the metal surface by conventional means, including brushing, dipping, rolling, and spraying, preferably spraying. Standard spraying techniques and equipment for spraying, such as air-atomized spraying, air spraying, airless spraying, high volume low pressure spraying, and electrostatic spraying, such as electrostatic bell application, and either manual or automated methods can be used. The method of the present invention can be carried out without the step of applying an adhesive material to the metal shell before applying the polyurethane composition.
[0047] The method of packaging a battery device of the present invention further comprises drying the applied polyurethane composition to form a packaging layer. The drying of the polyurethane composition can be carried out at a temperature of 100°C or less, 90°C or less, 80°C or less, 78°C or less, 75°C or less, 72°C or less, or even 70°C or less, while at the same time at room temperature (15-30°C), or at 50°C or more, 52°C or more, 55°C or more, 58°C or more, or even 60°C or more. The drying time can vary depending on the drying temperature, and can be, for example, approximately 30 minutes (min) or more, while at the same time 3 hours or less, 2 hours or less, or even 1 hour or less. When the polyurethane composition dries or hardens, it forms a polyurethane packaging layer. The formed packaging layer can have a dry film thickness of 30 micrometers (μm) or more, 35 μm or more, or even 40 μm or more, while at the same time 120 μm or less, 115 μm or less, 110 μm or less, 105 μm or less, or even 100 μm or less. The packaging layer can be attached directly to the surface of the metal shell without a layer of adhesive material between them. The packaging layer can provide a conformal coating enclosure for the battery device. The packaging layer provides sufficient flexibility to be wrapped around the metal shell and has the necessary electrical insulation and mechanical properties to provide the toughness and hermeticity required for the package. The packaging layer can function as an electrical insulation layer while providing a balanced set of properties to meet the requirements of the battery industry. The packaging layer can be 10 12 ("1E+12") ohm cm or more, 10 13 ("1E+13") ohm·cm or even 10 14The packaging layer is characterized by a volume resistivity (VR) of 1E+14 ohm·cm or greater; an impact resistance of 10 cm (0.91 kg) or greater, 40 cm or greater, 55 cm or greater, or even 60 cm or greater, and a chemical resistance of 100 times or greater. The packing layer may also provide an adhesion rating of 5B and / or a hardness of F or greater or H or greater. Preferably, the packaging layer also has a good appearance as indicated by a DOI of 74 or greater, 75 or greater, 76 or greater, 80 or greater, or even 85 or greater. The DOI measures the clarity of the reflected image on a surface (e.g., the surface of the packaging layer) and is an indication that the reflection is perfect and that the surface is free of haze or "orange peel". The present invention also relates to a method of insulating a battery device by applying a polyurethane composition and drying the applied polyurethane composition to form an electrically insulating layer having a VR of 1E+12 ohm·cm or greater, and optionally one or more of the above properties including chemical resistance, impact resistance, hardness, and DOI. These properties can be measured according to the test methods described in the Examples section below.
[0048] The present invention also provides a battery package (also referred to as a "battery enclosure" or "battery case") resulting from the method of the present invention. The battery package includes a battery device having a metal shell encapsulated by a packaging layer (or an electrically insulating layer). The battery package encloses or surrounds the battery device with the metal shell as an inner layer of the battery package and the packaging layer as an outer layer of the battery package. The battery packages useful in the present invention can be used in a variety of applications such as power sources for portable electronic power tools and vehicle applications including hybrid electric vehicles, plugs in hybrid electric vehicles, and fully electric vehicles. The battery packages can also be used to package devices for storing electrical energy generated from wind, water, or sun. EXAMPLES
[0049] Certain embodiments of the present invention are now illustrated in the following examples, in which all parts and percentages are by weight unless otherwise specified.
[0050] Styrene (ST), 2-ethylhexyl acrylate (EHA), methacrylic acid (MAA), acrylic acid (AA), and methyl methacrylate (MMA) are all available from Langyuan Chemical Co., Ltd.
[0051] Hydroxyethyl methacrylate (HEMA), n-dodecyl mercaptan (n-DDM), t-butyl hydroperoxide (t-BHP), ammonium persulfate (APS), isoascorbic acid (IAA), and ethylenediaminetetraacetic acid (EDTA) tetrasodium salt are all available from Sinopharm Chemical Reagent Co., Ltd.
[0052] Phosphoethyl methacrylate (PEM) and acetoacetoxyethyl methacrylate (AAEM) are available from Solvay.
[0053] DISPONIL Fes 993 (Fes 993), a non-reactive surfactant available from BASF, is a branched alcohol ethoxylate sulfate, sodium salt, having 11 ethylene oxide (EO) units.
[0054] DISPERBYK-190 dispersant (BYK-90) is available from BYK.
[0055] Tego Twin 4100 wetting agent is available from Evonik Industries.
[0056] BYK-345 wetting agent is available from BYK.
[0057] Ti-Pure R-706 titanium dioxide (pigment) is available from The Chemours Company.
[0058] TEGO Airex 902 W (902W) and TEGO Foamex 1488 defoamers are both available from Evonik Industries.
[0059] Desmodur N3600 hexamethylene diisocyanate trimer is available from Covestro.
[0060] Aquolin 268 water dispersible hexamethylene diisocyanate trimer is available from Wanhua.
[0061] UV-414 UV curable paint (100%) is available from Fangzhou High-tech Co., Ltd.
[0062] The following materials, including the alcohol alkoxylates in the table below, are all available from The Dow Chemical Company (OROTAN, DOWANOL, ACRYSOL, PROSPERSE, PRIMAL, and MAINCOTE are all trademarks of The Dow Chemical Company).
[0063] OROTAN™ 681 dispersant is available from The Dow Chemical Company.
[0064] DOWANOL™ DPnB dipropylene glycol n-butyl ether and DOWANOL PM propylene glycol methyl ether are used as coalescents.
[0065] DOWANOL PGDA propylene glycol diacetate and DOWANOL PMA glycol ether acetate are used as dilution solvents for the polyisocyanate.
[0066] ACRYSOL™ RM-8W, ACRYSOL RM-5000, and ACRYSOL RM-845 rheology modifiers are hydrophobically modified ethylene oxide urethanes (HEURs).
[0067] PROSPERSE™ 500 (P-500) secondary dispersion (47% solids) contains a hydroxyl-functional acrylic copolymer with 30% structural units of hydroxyethyl methacrylate.
[0068] PROSPERSE 200 (P-200) emulsion (40% solids) contains a hydroxyl-functional acrylic copolymer with 12% structural units of hydroxyethyl methacrylate.
[0069] MAINCOTE™ HG-54C emulsion (42% solids) contains a non-hydroxyl containing acrylic copolymer.
[0070] PRIMAL™ BINDER U-91 (91UD) (42% solids) is an aqueous dispersion of an aliphatic polyurethane. [Table 1]
[0071] The following standard analytical equipment and methods are used in the examples and for determining the properties and characteristics described herein.
[0072] Particle size measurement The particle size of the polymer particles in the aqueous dispersions was measured using a Brookhaven BI-90 Plus Particle Size Analyzer, which uses the technique of photon correlation spectroscopy (light scattering of sample particles). This method involved diluting two drops of the aqueous dispersion to be tested in 20 mL of 0.01 M sodium chloride (NaCl) solution and further diluting the resulting mixture in a sample cuvette to achieve the desired count rate (K) (e.g., K ranges from 250 to 500 counts / second for diameters ranging from 10 to 300 nm). The particle size of the aqueous polymer dispersions was then measured and reported as the Z-average diameter by intensity.
[0073] Tg measurement Five to ten milligrams (mg) of sample were analyzed in sealed aluminum pans on a TA Instruments DSC Q2000 equipped with an autosampler under nitrogen atmosphere. The DSC Tg measurements included three cycles including -40 to 180°C at 10°C / min (first cycle, followed by a 5 minute hold to erase the thermal history of the sample), 180 to -40°C at 10°C / min (second cycle), and -40 to 180°C at 10°C / min (third cycle). The Tg was obtained from the third cycle by taking the midpoint in the heat flow versus temperature transition as the Tg value.
[0074] GPC analysis GPC analysis of the polymers was generally performed on an Agilent 1200. Samples were dissolved in tetrahydrofuran (THF) / formic acid (FA) (5%) at a concentration of 2 mg / mL and then filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter prior to GPC analysis. GPC analysis was performed using the following conditions:
[0075] Columns: one PLgel GUARD column (10 μm, 50 millimeters (mm) × 7.5 mm), two Mixed B columns (7.8 mm × 300 mm) in tandem; column temperature: 40 °C; mobile phase: THF / FA (5%); flow rate: 1.0 mL / min; injection volume: 100 μL; detector: Agilent refractive index detector, 40 °C; and calibration curve: using PL Polystyrene I Narrow standards with molecular weights ranging from 2,329,000 to 580 g / mol, polynom 3 fitness.
[0076] Hardness Testing Pencil hardness testing was performed on coated steel panels (Q-panel R-46) according to ASTM D 3363 (2011). The hardness of the pencil lead was recorded when the pencil did not incise or chip the film. A hardness of F or better is acceptable.
[0077] Clearness of Image (DOI) Test DOI measurements were performed on coated aluminum panels (Q-panel R-46) according to ASTM D5767-18 (Standard Test Methods for Instrumental Measurement of Distinctness-of-Image Gloss of Coating Surfaces) using a BYK Gardener microwave scan meter (BYK-Gardner USA, Columbia, Md.). For each panel, the average of three separate readings was recorded as the DOI value. The higher the DOI, the better. If the DOI of the coating is too low to measure, the BYK Gardener microwave scan meter reading will read "Not Measurable, Matte >55" and will be recorded as "Not Measurable" in Table 3 below (when an object is viewed reflected in such a coating, the image will be unclear and distorted).
[0078] Solid content The solid content was measured by weighing 0.7±0.1g of sample (the wet weight of the sample is denoted as "W1") and placing it in an aluminum pan (the weight of the aluminum pan is denoted as "W2") in an oven at 150°C for 25 minutes, then cooling the aluminum pan containing the dried sample and weighing the total weight, denoted as "W3". The solid content of the sample is calculated as (W3-W2) / W1*100%.
[0079] Dry Film Thickness Test The dry film thickness (DFT) of the coated aluminum panels (Q-Panel A-46) was measured using a BYKO-Test 8500. The average of three separate readings was recorded.
[0080] Volume Resistivity (VR) Test VR testing was performed on coated aluminum panels (Q-panel A46) according to ASTM D 257-18. A Keithley 6517B electrometer was used in conjunction with a Keithley 8009 test fixture. The Keithley model 8009 test chamber was placed inside a blower oven capable of operating at high temperatures (up to 80° C.). VR was calculated by the following formula:
number
[0081] Impact resistance test Impact resistance was evaluated on coated aluminum panels (Q-panel A46) using a BYK GARDNER impact tester according to ASTM D 5420-10. Results are reported in cm (0.91 kg).
[0082] Chemical Resistance Test Methyl ethyl ketone (MEK) double rub resistance was used to evaluate the chemical resistance of the coating films. MEK double rub resistance testing was performed on coated aluminum panels (Q-panel A46) according to ASTM D5402 (1999). An Atlas Crockmeter was used to perform the double rubs and cheesecloth was used to retain sufficient MEK solution. The number of double rubs it took for the coating film to first break was recorded. Two measurements were made for each coating film.
[0083] Synthesis of polymer dispersion 1 (PD1) A monomer emulsion was prepared by mixing 318 grams (g) of deionized (DI) water, Fes993 surfactant (23 g, 30%), MMA (149 g), ST (306 g), EHA (176 g), HEMA (304 g), AAEM (51 g), MAA (16 g), PEM (16 g), and n-DDM (21 g). DI water (600 g) and Fes993 surfactant (43 g, 30%) were charged to a 5-liter multi-neck flask equipped with mechanical stirring. The contents of the flask were heated to 90° C. under a nitrogen atmosphere. Ammonia (2.5 g, 25%) in DI water (16.9 g), monomer emulsion (29 g), and ammonium persulfate (APS) (2.0 g) in DI water (16.9 g) were then added to the stirred flask, followed by a DI water (3.75 g) rinse. The remaining monomer emulsion was further added over 160 minutes at 86° C., followed by a DI water (30 g) rinse. At the end of the polymerization, FeSO4.7H2O (0.005 g) in DI water (15.75 g) mixed with EDTA tetrasodium salt (0.005 g) in DI water (15.75 g), a solution of t-BHP (70%, 1.6 g) in DI water (32.8 g), a solution of IAA (0.8 g) in DI water (34.3 g), a solution of t-BHP (0.8 g) in DI water (16.4 g), and a solution of IAA (0.4 g) in DI water (17.2 g) were all added to the flask at 60° C., followed by the addition of ammonia (7.0 g, 25%) in DI water (16.65 g) at 50° C. to obtain an aqueous dispersion.
[0084] Synthesis of polymer dispersion 2 (PD2) A monomer emulsion was prepared by mixing DI water (271 g), Fes993 surfactant (40.4 g, 30%), MMA (144 g), ST (281 g), EHA (161 g), HEMA (278 g), AAEM (46 g), AA (12 g), PEM (7 g), and n-DDM (37 g). DI water (568 g) and Fes993 surfactant (20 g, 30%) were charged to a 5 liter multi-neck flask equipped with mechanical stirring. The contents of the flask were heated to 90° C. under a nitrogen atmosphere. Aqueous ammonia (2.3 g, 25%) in DI water (18 g), monomer emulsion (76 g), and APS (1.9 g) in DI water (22 g) were then added to the stirred flask, followed by a DI water (4 g) rinse. The remaining monomer emulsion was further added over 160 minutes at 86° C., followed by a DI water (30 g) rinse. At the end of the polymerization, a solution of FeSO4.7H2O (0.005 g) in DI water (15.75 g) mixed with EDTA tetrasodium salt (0.005 g) in DI water (15.75 g), a solution of t-BHP (1.4 g, 70% aqueous solution) in DI water (26 g), a solution of IAA (0.7 g) in DI water (26 g), a solution of t-BHP (0.4 g) in DI water (8 g), and a solution of IAA (0.2 g) in DI water (8 g) were all added to the flask at 60° C., followed by the addition of ammonia (7.0 g, 25%) in DI water (16.65 g) at 50° C. to obtain an aqueous dispersion.
[0085] Synthesis of polymer dispersion 3 (PD3) PD3 was prepared similarly to the synthesis of PD2, except that a monomer emulsion was prepared by mixing DI water (271 g), Fes993 surfactant (30%) (40.4 g), MMA (144 g), ST (281 g), EHA (161 g), HEMA (278 g), AAEM (46 g), AA (12 g), PEM (7 g), and n-DDM (9 g).
[0086] Synthesis of polymer dispersion 4 (PD4) PD4 was prepared similarly to the synthesis of PD2, except that a monomer emulsion was prepared by mixing DI water (271 g), Fes993 surfactant (40.4 g, 30%), MMA (146 g), ST (363 g), EHA (78 g), HEMA (278 g), AAEM (46 g), AA (12 g), PEM (7 g), and n-DDM (19 g).
[0087] Synthesis of polymer dispersion 5 (PD5) PD5 was prepared similarly to the synthesis of PD2, except that a monomer emulsion was prepared by mixing DI water (271 g), Fes993 surfactant (30%) (40.4 g), MMA (31 g), ST (282 g), EHA (275 g), HEMA (278 g), AAEM (46 g), AA (12 g), PEM (7 g), and n-DDM (19 g).
[0088] The properties of the resulting emulsion polymer dispersion are shown in Table 1. [Table 2] 1 Viscosity measured by Brookfield Viscometer DV-I Primer (60 rpm, spindle #2) 2 Tg measured by DSC, 3 The M obtained from the above GPC analysis n and Mw.
[0089] Packaging material compositions of Examples (Ex) 1 to 10, 15 to 18, and 20 to 24 and Comparative Examples (Comp) C, D, and E Examples 1-10, 15-18, and 20-24 and Comparative Example E were prepared based on the formulations shown in Table 2-1. Comparative Examples C and D were prepared based on the formulations shown in Table 2-2. The types of alcohol alkoxylates (AOs) used to prepare the packaging material compositions are listed in Table 3. For the preparation of the two-component compositions, the components for preparing the grind were mixed using a high-speed Cowles disperser at 1,500 revolutions per minute (rpm) for 30 minutes to form a grind. The components in the letdown were then added to the grind using a conventional lab mixer to obtain Part A. Part A was left overnight, and then Part B was added to Part A using a high-speed disperser at 600 rpm for 10 minutes to form each packaging material composition. For the preparation of the one-component packaging material compositions of Comparative Examples C and E, the components were mixed using a high-speed Cowles disperser at 1,500 rpm for 30 minutes to obtain a composition.
[0090] Immediately after mixing all the components therein, the resulting packaging material composition was applied onto the surface of a metal substrate (aluminum or steel panel) by spraying. After applying the wet paint film to the substrate, the resulting panel was dried under the following conditions: dried at room temperature for 20 minutes, then dried at 60°C for 40 minutes, and finally dried at room temperature for 7 days. The resulting coated panels with coating film (i.e., packaging layer) thickness ranging from 30 μm to 200 μm were evaluated according to the test methods described above.
[0091] Comparative Examples A and B The UV-414 UV curable formulation was applied on the surface of metal substrate (aluminum or steel panel) by spraying at different film thickness. Immediately after spraying, the obtained panel was placed in a UV curing machine (Heraeus F300S, xenon lamp) and irradiated for 10 seconds. The obtained coated panels with dry film thickness of 60 μm and 100 μm for Comparative Examples A and B, respectively, were evaluated according to the test method described in the Examples section above. [Table 3] [Table 4]
[0092] Example 11 Packaging Material Composition Example 11 was prepared similarly to Example 6, except that the amounts of alcohol alkoxylate and deionized water used in the dilution step were 1.6 g and 3.81 g, respectively.
[0093] Example 12 Packaging Material Composition Example 12 was prepared similarly to Example 6, except that the amounts of alcohol alkoxylate and deionized water used in the dilution step were 1.2 g and 4.21 g, respectively.
[0094] Example 13 Packaging Material Composition Example 13 was prepared similarly to Example 6, except that the amounts of alcohol alkoxylate and deionized water used in the dilution step were 1 g and 4.41 g, respectively.
[0095] Example 14 Packaging Material Composition Example 14 was prepared similarly to Example 6, except that the amounts of alcohol alkoxylate and deionized water used in the dilution step were 0.5 g and 4.91 g, respectively.
[0096] Example 19 Packaging Material Composition Example 19 was prepared similarly to Example 6, except that the amount of DI water used in the dilution step was 5.41 grams and no alcohol alkoxylate was used.
[0097] The above obtained packaging material compositions were evaluated according to the above test methods, and the results are shown in Table 3. As shown in Table 3, all of Examples 1-24 provided packaging layers with good electrical insulation as indicated by volume resistivity of 1E+12 ohm·cm or more, good impact resistance (10 cm or more at 0.91 kg), sufficient chemical resistance (100 times or more), adhesion rating of 5B, and pencil hardness of F or more. In particular, Examples 6-18, which include hydroxyl-functional emulsion polymers and specific alcohol alkoxylates, provided even better electrical insulation as indicated by volume resistivity of 1+E13 ohm·cm or more, or even 1E+14 ohm·cm or more, and better impact resistance. Furthermore, Examples 1-18 provided packaging layers with higher DOI (≧74). In contrast, the packaging layer of Comparative Example A with a DFT of 60 μm formed from a UV-cured coating provided undesirably low VR and poor impact resistance. The packaging layer of Comparative Example B with a DFT of 100 μm formed by UV-cured coating showed poor impact resistance. Packaging layers made from the one-component acrylic system HG-54C (Comparative Example C), the two-component PU system P-200 containing 12% HEMA structural units (Comparative Example D), or the one-component PU dispersion 91UD (Comparative Example E) all showed poor chemical resistance and poor hardness. [Table 5] 1 PAO dosage: by weight based on dry weight of emulsion polymer; 2 nm - Not measurable.
Claims
1. 1. A method for packaging a battery device with a metal shell, comprising: applying a water-based two-component polyurethane composition to the metal shell of the battery device; drying the applied polyurethane composition to form a packaging layer, The polyurethane composition comprises: (A) an aqueous dispersion comprising a hydroxyl-functional polymer, the hydroxyl-functional polymer comprising, based on the weight of the hydroxyl-functional polymer, 20% to 50% by weight of structural units of a hydroxy-functional alkyl (meth)acrylate, 0.1% to 10% by weight of structural units of an acid monomer, a salt thereof, or a mixture thereof, and a monoethylenically unsaturated nonionic monomer; (B) a polyisocyanate, forming a packaging layer, the packaging layer having a thickness of 30 μm to 120 μm, and the packaging layer being directly attached to a surface of the metal shell without a layer of adhesive material therebetween.
2. The method of claim 1, wherein drying of the polyurethane composition is carried out at a temperature of from 50°C to 80°C.
3. The method of claim 1 or 2, wherein the hydroxyl functional polymer is an emulsion polymer.
4. The aqueous dispersion (A) further comprises 2% to 20% by weight, based on the weight of the emulsion polymer, of an alcohol alkoxylate, the alcohol alkoxylate having a molecular weight of 1,000 g / mole or less, and a copolymer having the formula (I): R 1 -O-(CHR 3 -CHR 4 -O) x -(CH 2 CH 2 -O) y -(CHR 5 -CHR 6 -O) z -R 2 (In the formula, R 1 is C 6 ~C 18 is a branched aliphatic group, R 2 is hydrogen, C 1 ~C 4 is a linear or branched aliphatic group or benzyl; R 3 and R 4 are each independently hydrogen or C 1 ~C 6 an aliphatic group, where R 3 and R 4 contains 1 to 6 carbon atoms in total, R 5 and R 6 are each independently hydrogen or C 1 ~C 6 an aliphatic group, where R 5 and R 6 4. The method of claim 3, wherein x, y, z, and z are independently selected from the group consisting of 1 to 6 carbon atoms in total, x is an average value ranging from 0 to 10, y is an average value ranging from 5 to 15, and z is an average value ranging from 0 to 5, with the proviso that x+z>0, and wherein the alcohol alkoxylate comprises 25% to 75% by weight ethylene oxide units, based on the weight of the alcohol alkoxylate.
5. The method of any one of claims 1 to 4, wherein the hydroxyl functional polymer has a weight average molecular weight of 50,000 g / mole or less.
6. 6. The method of any one of claims 1 to 5, wherein the hydroxy-functional alkyl (meth)acrylate is selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, or mixtures thereof.
7. The method of any one of claims 1 to 6, wherein the hydroxyl functional polymer has a glass transition temperature of 10 to 80°C.
8. The packaging layer has a thickness of 30 μm to 120 μm and is 12 The method according to any one of claims 1 to 7, wherein the electrically insulating layer has a volume resistivity of ohm.cm or more and / or an image definition of 74 or more.
9. The method according to any one of claims 1 to 8, wherein the metal shell is a layer of metal foil.
Citation Information
Patent Citations
Barrier layer soft package film of polymer lithium ion battery
CN102358068A
Nonaqueous battery laminate
JP2012156027A
Gass barrier laminate film
JP2014069389A
Polyurethane adhesive for battery packaging material, battery packaging material, battery container, and battery
JP2014185317A
battery coating
JP2017505507A